Vertical modeling of the nitrogen cycle in the eastern tropical South Pacific oxygen deficient zone using high‐resolution concentration and isotope measurements. Issue 11 (10th November 2016) - Peters, Brian D.; Babbin, Andrew R.; Lettmann, Karsten A.; Mordy, Calvin W.; Ulloa, Osvaldo; Ward, Bess B.; Casciotti, Karen L.
Abstract: Marine oxygen deficient zones (ODZs) have long been identified as sites of fixed nitrogen (N) loss. However, the mechanisms and rates of N loss have been debated, and traditional methods for measuring these rates are labor‐intensive and may miss hot spots in spatially and temporally variable environments. Here we estimate rates of heterotrophic nitrate reduction, heterotrophic nitrite reduction (denitrification), nitrite oxidation, and anaerobic ammonium oxidation (anammox) at a coastal site in the eastern tropical South Pacific (ETSP) ODZ based on high‐resolution concentration and natural abundance stable isotope measurements of nitrate (NO3 − ) and nitrite (NO2 − ). These measurements were used to estimate process rates using a two‐step inverse modeling approach. The modeled rates were sensitive to assumed isotope effects for NO3 − reduction and NO2 − oxidation. Nevertheless, we addressed two questions surrounding the fates of NO2 − in the ODZ: (1) Is NO2 − being primarily reduced to N2 or oxidized to NO3 − in the ODZ? and (2) what are the contributions of anammox and denitrification to NO2 − removal? Depth‐integrated rates from the model suggest that 72–88% of the NO2 − produced in the ODZ was oxidized back to NO3 −, while 12–28% of NO2 − was reduced to N2 . Furthermore, our model suggested that 36–74% of NO2 − loss was due to anammox, with the remainder due to denitrification. These model results generally agreed with previously measured rates, though with a large range of uncertainty, and they provide a long‐term integrated view that compliments incubation experiments to obtain a broader picture of N cycling in ODZs. Key Points: Nitrate and nitrite isotopes can be used in inverse 1‐D modeling to predict rates of nitrogen cycle processes in ODZs Close coupling of nitrate reduction and nitrite oxidation is suggested by model results Tighter constraints on isotope effects for nitrate reduction and nitrite oxidation are greatly needed